Empowering Autonomous Islamic Religious Education Learners With Technology-Enhanced Tools To Improve Performance And Self-Motivation - Arafah, Abdul Latief Arung; Jiao, Deng; Selvia , Devi Sela Eka; Wang, Yuanyuan; Halim, Chandra (Journal Neosantara Hybrid Learning, 2024)
Islamic religious education is an important part of the curriculum in many countries with a majority Muslim population. However, challenges in teaching Islam are often related to limited resources and lack of student involvement. The use of technology in learning can be a solution to improve the quality of Islamic learning and motivate students independently. This research also aims to determine the extent to which the application of gamification techniques can empower learners in the context of Islamic religious education. This research uses an experimental approach. Data about students' academic performance and level of self-motivation were collected through academic tests and questionnaires before and after treatment. The research results show that the use of technology-enhanced learning tools in Islamic learning significantly improves students' academic performance. Apart from that, it was found that the application of gamification techniques in learning also had a positive impact on students' self-motivation. Students who are involved in learning that uses technology and gamification techniques show a higher level of motivation in studying Islamic religious material compared to students who follow conventional learning methods. The conclusion of this research explains that the use of technology-enhanced learning tools and gamification techniques can be an effective strategy in improving students' academic performance and self-motivation in learning Islamic religion. The implementation of technology in Islamic learning not only enriches the learning experience, but also empowers students to become more active and enthusiastic autonomous learners.